2020
DOI: 10.1007/978-3-030-25838-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies of Migrant Ex-partners. Does Work, Family, or a New Partner Help You Through the Dark Times?

Abstract: This study focuses on financial consequences of a separation for migrant ex-partners. International literature on economic consequences has well documented the gender effects in the consequences of splitting up or the differences between former married and cohabiting couples. Building on these insights, this chapter focuses on the heterogeneity in couples in migration status and origin group. Using data from the Belgian Crossroads Bank of Social Security, we look at financial consequences after a break-up for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…On average, women are financially worse off when a union comes to an end, whether in the traditional divorce research (Hoffman and Duncan, 1988;Peterson, 1996) or the more recent extension into relationship dissolution in general (Andreß et al, 2006;Brewer and Nandi, 2014). While there is considerable difference in the size of the financial downturn, that it is there continues to be found even in the most recent research (Mortelmans et al, 2020). Additionally, Thielemans and Mortelmans (2019) found that the probability that Flemish women increase their employment is up to seven times higher surrounding the time of a couple's factual separation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, women are financially worse off when a union comes to an end, whether in the traditional divorce research (Hoffman and Duncan, 1988;Peterson, 1996) or the more recent extension into relationship dissolution in general (Andreß et al, 2006;Brewer and Nandi, 2014). While there is considerable difference in the size of the financial downturn, that it is there continues to be found even in the most recent research (Mortelmans et al, 2020). Additionally, Thielemans and Mortelmans (2019) found that the probability that Flemish women increase their employment is up to seven times higher surrounding the time of a couple's factual separation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, concerning employment, evidence has been found that women increase their employment after divorce (Brewer and Nandi, 2014;Raz-Yurovich, 2013). Other research found that those who did were financially significantly better off than those who did not (Bro ¨ckel and Andreß, 2015;De Regt et al, 2013;De Vaus et al, 2017;Fokkema, 2000;Jansen et al, 2009;Mortelmans et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We look at how the boomerang effect plays out differently in the lives of fathers and mothers of Belgian, Turkish, and Moroccan origin, and take the migration background of the ex-partner into account. Second, we investigate whether economic and family differentials within these origin groups influence the likelihood of returning to the parental home (Mortelmans et al 2019).…”
Section: Introductionmentioning
confidence: 99%